2021
DOI: 10.3390/agronomy11061119
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction and Genotype-by-Environment Interaction Analysis of Crown and Stem Rust in Ryegrasses in European Multi-Site Trials

Abstract: Climate change calls for novel approaches to include environmental effects in future breeding programs for forage crops. A set of ryegrasses (Lolium) varieties was evaluated in multiple European environments for crown rust (Puccinia coronata f. sp. lolii) and stem rust (P. graminis f. sp. graminicola) resistance. Additive Main Effect and Multiplicative Interaction (AMMI) analysis revealed significant genotype (G) and environment (E) effects as well as the interaction of both factors (G × E). Genotypes plus Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Including GxE in genomic prediction has been investigated in many crops including maize (Windhausen et al, 2012;Malosetti et al, 2013a), barley (Malosetti et al, 2016), ryegrass (Fois et al, 2021) and coffee (Ferrão et al, 2019), to name just a few. Due to its ploidy and heterozygosity, GxE interactions in tetraploid potato has been theorized to be substantial (Jansky and Spooner, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including GxE in genomic prediction has been investigated in many crops including maize (Windhausen et al, 2012;Malosetti et al, 2013a), barley (Malosetti et al, 2016), ryegrass (Fois et al, 2021) and coffee (Ferrão et al, 2019), to name just a few. Due to its ploidy and heterozygosity, GxE interactions in tetraploid potato has been theorized to be substantial (Jansky and Spooner, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In GP, it is typical to combine various sources of information, in an attempt to increase prediction accuracy. In plant breeding, multi-environment trials are commonplace and therefore the combining of information from multiple environments has been applied across a variety of crops and shown to improve prediction accuracy (Windhausen et al, 2012;Malosetti et al, 2013aMalosetti et al, , 2016Ferrão et al, 2019;Fois et al, 2021). In animals, combining information across different breeds or subspecies is of special interest to breeders, and has shown to be beneficial (de Roos et al, 2009;Raymond et al, 2018a).…”
Section: Combining Information To Increase Prediction Accuracymentioning
confidence: 99%
“…Furthermore, QTL analysis and quantitative genetics studies aimed at identifying genomic regions associated with quantitative traits of interest in breeding and/or adaptive traits [ 63 ], can now be performed with greater resolution as most genetic markers can be anchored to the chromosomes. In addition, the comprehensive gene set combined with scaffold contiguity supports identification of genes flanking genetic markers in search of the molecular mechanisms underlying agronomic traits [ 64 ], adaptive traits, or survival strategies [ 65 – 67 ]. Furthermore, the new, advanced perennial ryegrass reference genome and annotation presented here, might significantly expand the potential of pan-genomic studies in the Festuca-Lolium complex.…”
Section: Discussionmentioning
confidence: 99%
“…The SI consists of 14 original research contributions focusing on diverse crops including cereals (winter wheat, maize, rice and ryegrass) [1][2][3][4][5], legumes (grass pea, soybean, chickpea) [6][7][8], rapeseed oil [9], eggplant [10], blackgram [11], bambara groundnut [12], strawberry [13] and sugarcane [14]. Investigations combined different types of germplasm, study strategies and application of statistical models.…”
mentioning
confidence: 99%
“…Environmental effects on biotic stress resistance due to crown and stem rust were instead determined in 54 ryegrass accessions grown across 34 European locations in three cycles performed in 12 years [5]. Such comprehensive work highlighted the effect of the environment on natural infections and indicated that the tetraploid varieties are better performing than diploid ones; furthermore, it showed how the large number of observations allowed better accuracy in trait performance prediction.…”
mentioning
confidence: 99%